TINJAUAN TERHADAP PENERAPAN METODE TASMI’ DAN MURAJA’AH DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR’AN (Studi Kualitatif Deskriptif pada Siswa SDIT Thariq Bin Ziyad Jatimulya Bekasi) - Deni Sanjaya; Abdul Khoir HS (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2020)
This zstudy aims to describe the implementation of Tahfidz Al-Qur’an learning at SDIT Tariq BinZiyad. This program is a program to memorize the Qur’an which is periodically tested for each juzand those who pass will get a certificate. So that the ability to memorize the Qur’an of each studentcan be measured. Therefore, the authors azre interested in conducting research at the SDIT Tariq BinZiyad school on how to apply the tasmi’ and muraja’ah methods in improving the ability to memorizethe Qur’an, as well as what factors support and hinder the application of the tasmi’ and muraja’ahmethods. the. To answer the questions above, the author uses a descriptive qualitative methodwhich has natural characteristics as a direct data source, while the techniques used are interviews,observation, and documentation. The data are sourced from: Principals, Al-Qur’an Coordinators, Al-Qur’an Teachers and SDIT Tariq Bin Ziyad students. From the results of observations and interviews,the authors reveal the research findings of the process of implementing tahfidz Al-Qur’an learningat SDIT Tariq Bin Ziyad, namely: It is carried out every Tuesday, Wednesday, and Thursday. Theimplementation process is: All students are divided into several groups. Each group consists of oneteacher, and a maximum of 25 students according to their level. Then all students sit down by makinghalaqoh. Then the teacher started by reading the opening prayer and continued with muraja’ah. Afterthe muraja’ah, the teacher gives an example of reading the verse correctly first to the students. Thenstudents imitate repeatedly, until they are correct and fluent. After that, it ends with a rote deposit to theteacher and a closing prayer. As for the achievement of students’ abilities in memorizing the Qur’anfrom 710 students in 2019, students who were able to memorize the Qur’an were 3 Juz, namely 5%or 35 students. The success of learning Tahfidz Al-Qur’an cannot be separated from the supportingfactors such as certified teachers, adequate facilities, and a conducive classroom environment. Inaddition to supporting factors, there are also factors that can hinder the success of the tahfidz activityprocess such as limited time allocation, differences in the character and abilities of children, and thepresence of teachers who are unable to attend.